Sensory Difficulties in Children With an FMR1 Premutation - Raspa, Melissa; Wylie, Amanda; Wheeler, Anne C.; Kolacz, Jacek; Edwards, Anne; Heilman, Keri; Porges, Stephen W. (Frontiers in Genetics, 2018)
Abnormal sensory processing is one of the core characteristics of the fragile X phenotype. Studies of young children with fragile X syndrome (FXS) and the FMR1 premutation have shown sensory challenges as early as infancy and into early childhood. This study sought to examine differences in sensory difficulties in children with an FMR1 premutation compared with children with FXS and typically developing children. We conducted an online survey of 176 parents of affected children (FXS or FMR1 premutation). Most respondents were mothers who are Caucasian (86%), have a 4-year college or graduate degree (68%), and are married (92%). Children ranged in age from 5 to 18, with a mean age of 13.0 years (3.3 SD). Participants completed the BBC Sensory Scales, a 50-item Likert-type scale (1 = Almost Always, 4 = Almost Never) comprised of 8 subscales that assessed auditory processing, visual processing, tactile processing, and eating and feeding behaviors. Mean scores were calculated for the items and each of the subscales. Non-parametric tests examined differences in child and family-level variables. Across all BBCSS subscales, children with an FMR1 premutation displayed more sensory challenges than typically developing children. For six out of the eight subscales, children with the full mutation had the lowest scores indicating more sensory challenges, but this was closely followed by children with an FMR1 premutation. Fragile X status was associated with seven of the eight subscales; children with an FMR1 premutation did not differ from children with FXS on any of the subscales but had more digestive problems than children with no fragile X. Gender, autism status, and family income were also related to sensory sensitivities. In conclusion, these data provide further evidence that some children with an FMR1 premutation experience sensory difficulties that are similar to children with FXS but different than typically developing children.